Determinants of Poverty in East Java: Education, Unemployment, and Minimum Wage - Alfin, Laila Choirummin; Boedirochminarni, Arfida (Global Economic, Social, and Development Review, 2025)
This study aims to analyze the effect of average school years, open unemployment rate, and minimum wage on the number of poor people in East Java Province from 2014-2023. The research method used is quantitative with a descriptive approach, using panel data regression covering 38 districts/cities. The data analyzed were sourced from the East Java Badan Pusat Statistik (BPS), including the number of poor people, average school years, open unemployment rate, and minimum wage. The analysis shows that average years of schooling have a significant negative effect on poverty. Although the minimum wage hurts poverty, the effect is minimal. These findings emphasize the importance of improving education and reducing unemployment as the main strategies for poverty alleviation in East Java.